Evaluation of Yield Potential and Dry Matter Content of Promising Clones of Orange Fleshed Sweetpotato Rich in Betacarotene - Febria Cahya Indriani; Joko Restuono; Wiwit Rahajeng; Yuliantoro Baliadi; Made Jana Mejaya (Dwijendra University, 2020)
Public awareness of foods that have physiological functions for health is increasing. Consumption of orange fleshed sweetpotato not only meets carbohydrate requirements but also beta-carotene which is good for eye health. The aim of this reserach was to evaluate the yield potential and levels of dry matter content of promising clones of orange fleshed sweetpotato rich in beta-carotene. The study was conducted in Malang, East Java in Dry Season II 2016. Genetic materials used were 20 sweetpotato clones, including Beta-1 and Beta-2 varieties as a check. The treatment design used a randomized block design with three replications. The results showed that the clones tested had a potential yield ranging from 20.9 - 35.1 t/ha with an average of 25.2 t/ha. There were three clones had a higher yield potential than the check varieties Beta-1 and Beta-2. Dry matter content ranged from 17.0 - 31.6% with an average of 25.7%. Fifteen clones had higher levels of dry matter content than check varieties Beta-1 and Beta-2. MSU 14018-06, MSU 14001-20 and MSU 14027-02 clones had high yield potential and dry matter content. All three clones have the opportunity to be released as new superior varieties of orange fleshed sweet potato rich in beta-carotene.